Defensins and the convergent evolution of platypus and reptile venom genes. - Whittington, C; Papenfuss, A; Bansal, P; Torres, A; Wong, E; Deakin, J; Graves, T; Alsop, A; Schatzkamer, K; Kremitzki, C; Ponting, C; Temple-Smith, P; et al. (2008)
When the platypus (Ornithorhynchus anatinus) was first discovered, it was thought to be a taxidermist's hoax, as it has a blend of mammalian and reptilian features. It is a most remarkable mammal, not only because it lays eggs but also because it is venomous. Rather than delivering venom through a bite, as do snakes and shrews, male platypuses have venomous spurs on each hind leg. The platypus genome sequence provides a unique opportunity to unravel the evolutionary history of many of these interesting features. While searching the platypus genome for the sequences of antimicrobial defensin genes, we identified three Ornithorhynchus venom defensin-like peptide (OvDLP) genes, which produce the major components of platypus venom. We show that gene duplication and subsequent functional diversification of beta-defensins gave rise to these platypus OvDLPs. The OvDLP genes are located adjacent to the beta-defensins and share similar gene organization and peptide structures. Intriguingly, some species of snakes and lizards also produce venoms containing similar molecules called crotamines and crotamine-like peptides. This led us to trace the evolutionary origins of other components of platypus and reptile venom. Here we show that several venom components have evolved separately in the platypus and reptiles. Convergent evolution has repeatedly selected genes coding for proteins containing specific structural motifs as templates for venom molecules.